Partners in Health - Centre for Access to Services in English (CASE) (2020)

In celebration of Early Childhood Week, the Community Health and Social Services Network is pleased to present : Supporting the Well-being of Young Children in English-speaking Communities! - Community Health and Social Services Network (CHSSN) (2020)

QCGN Opposes Holding School Board Elections in Red Zones - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).

Forum sur les perspectives jeunesse : orientations professionnelles et éducatives dans le monde post-COVID-19 - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
La jeunesse va (globalement) bien ! Ce message a été exprimé haut et fort lors d’une discussion captivante entre intellectuels, éducateurs, étudiants et conférenciers passionnés, qui s’est tenue virtuellement le 25 octobre 2020 dans le cadre du Forum sur les perspectives jeunesse de l’Université Concordia. L’événement a eu lieu à l’initiative du Réseau de recherche sur les communautés québécoises d’expression anglaise, par l’entremise de sa Table d’éducation interordres et en collaboration avec Youth 4 Youth Québec et le Centre de ressources de la communauté noire. Cette année, le forum avait un thème bien particulier : Orientations professionnelles et éducatives dans le monde post-COVID-19. En résumé, l’occasion a été donnée aux étudiants de saisir les nou- velles réalités de ce « monde d’après » afin qu’ils sachent comment s’engager sur la voie parfois déconcertante qui s’ouvre à eux. Alerte au divulgâcheur : tout va bien aller (mais il nous faudra procéder à quelques ajustements).

Forum for Youth Insights 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

Rapport annual 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

EPCA Welcomes New, Long Overdue, School Measures - English Parents' Committee Association (EPCA) (2020)

Supporting English Schools in Quebec Through the Pandemic - Advisory Board on English Education (2020)
The Advisory Board on English Education (ABEE) wrote to the Minister in June, 2020 regarding the return to school. Because little has changed since then among the concerns it raised, we urge the Minister to refer back to that document, included with this letter for your convenience. In September, ABEE met virtually to assess the situation in English-language schools and centres now that they are in operation after a six-month hiatus. In the words of one member, there were “different perspectives from different people with different responsibilities but all focused on how to play our part to make this work for our students, their families and our colleagues.” The discussion was wide-ranging, but several themes emerged that we respectfully share with the Minister.

Un soutien aux écoles anglaises durant la pandémie - Advisory Board on English Education (2020)
En juin 2020, la Commission de l’éducation en langue anglaise (CELA) a adressé au ministre de l’Éducation un mémoire concernant la rentrée scolaire. Puisque la plupart des inquiétudes qui y ont été soulevées persistent, nous prions le ministre de revoir ce document, que nous joignons à toutes fins utiles aux présentes. En septembre, les membres de la CELA se sont réunis en ligne pour évaluer la situation dans les écoles et centres anglophones, qui ont repris leurs activités après six mois d’interruption. Pour citer une des personnes présentes, « différents points y ont été exprimés par différents intervenants, mais tous s’articulaient autour du rôle que nous devons jouer dans l’instauration de solutions qui fonctionnent pour nos élèves, leur famille et nos collègues ». Malgré la portée générale des discussions, plusieurs thèmes sont ressortis, et nous prions le ministre de bien vouloir en prendre connaissance.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Fall Colours Acoustic Concert - Cancelled Due to COVID-19 - Centre for Access to Services in English (CASE) (2020)

CAMI Newsletter - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Back to School Plan : Working Together for a Serene and Safe Return to School - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Plan pour la rentrée scolaire : Travailler ensemble pour une rentrée sereine et sécuritaire - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Neighbours Newsletter : August 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

Reisaction : Our Response to Covid-19 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

September Return to School : Parents Must Be Involved in Process - English Parents' Committee Association (EPCA) (2020)

Impact of Confinement on English-speaking Families - Community Health and Social Services Network (CHSSN) (2020)

Deconfinement Guidelines : What You Should Know in Times of Crisis - Seniors Action Quebec (SAQ) (2020)

Returning to School in the English Education System in Uncertain Times - Advisory Board on English Education (2020)
The sudden and widespread occurrence of COVID-19 has pointed out the great disparities across the province of Québec, such as the different situations between the cities and the regions, and also between sectors of the population within these settings. These differences have resulted in different policy decisions, such as when—or whether—to reopen schools, and we commend the Minister for applying local solutions to local situations. We hope this strategy will continue during the uncertainty that will apply to the probable second wave of the pandemic predicted for the Fall, and we welcome the possibility of different scenarios proposed in the working document on resumption of school for all in September. An unwelcome result of the rapidly changing situation and the need for quick decisions is the appearance of hasty, spontaneous decisions that are not conveyed appropriately to the educational partners who must respond to them. Policy -makers can react quickly. Systems can not. Announcing a policy then modifying or reversing it causes stress and confusion, especially when those who must implement the policy—including principals and teachers—feel excluded from the process.

Une rentrée sous le signe de l’incertitude dans le réseau scolaire anglophone - Advisory Board on English Education (2020)
L’apparition et la propagation soudaines de la COVID-19 ont mis en lumière de grandes disparités dans tout le Québec, notamment entre villes et régions, mais également entre divers segments de la population urbaine ou rurale. Ces disparités ont d’ailleurs mené à des décisions différentes, par exemple quant à la réouverture des écoles, et il y a lieu de saluer le ministre pour l’application de solutions locales à des situations locales. Nous espérons que cette stratégie sera maintenue pendant la période d’incertitude qui ne manquera pas de ressurgir avec la probable deuxième vague de la pandémie, prévue à l’automne . Nous accueillons favorablement la possibilité qu’il y ait différents scénarios, comme cela est proposé dans le document de travail sur la rentrée scolaire pour tous en septembre prochain. En revanche, l’évolution rapide de la situation et la nécessité d’agir promptement ont aussi comme résultat fâcheux quelques décisions spontanées et hâtives, qui ne sont pas transmises correctement aux partenaires du monde de l’éducation qui doivent pourtant y donner suite. Si les décideurs peuvent réagir rapidement, les systèmes ne le peuvent pas. Annoncer une politique, puis la modifier ou l’annuler est source de stress et de confusion, en particulier quand ceux qui doivent l’appliquer, dont les directeurs et les enseignants, se sentent exclus du processus.

COVID-19 Survey Report - Gaumond, Annie (Literacy Quebec, 2020)
On June 16, 2020, Literacy Quebec sent out an online survey to 11 member organizations. We asked about the needs and challenges of students, volunteers, and the organization, as well as the experience of working remotely during the COVID-19 pandemic. The survey closed on June 30, 2020 with a 100% response rate. We are pleased to share the summarized responses.

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

Les élections des écoles anglophones doivent être retardées - Garner, Linton (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

COVID-19 : Reopening of Schools : EPCA Survey to Parents - English Parents' Committee Association (EPCA) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Jamaica Association of Montreal Newsletter : Special Edition: May 2020 : Volume 16.1 - Jamaica Association of Montreal (JAM) (2020)

The QFHSA Back-to-School Survey : What Our Members Had To Say - Quebec Federation of Home and School Associations (QFHSA) (2020)
The Quebec Federation of Home and School Associations (QFHSA) surveyed its members recently on the Quebec government’s plan to reopen schools this spring. We learned that a small minority of parents (16.74%) plan to send their children back to school when it reopens. Of those who intend to keep their children at home, 65.5% are opting for distance learning; and 30%, home-schooling.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Gradual Reopening of Elementary Schools - English Parents' Committee Association (EPCA) (2020)

Reopening of Schools - English Parents' Committee Association (EPCA) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

QCGN Welcomes Wider Distribution of COVID-19 Self-care Guide to English Speaking Quebecers - Quebec Community Groups Network (QCGN) (2020)

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

[Update to Parents Regarding School Reopenings] - English Parents' Committee Association (EPCA) (2020)

Seniors Action Quebec Statement on Situation at Residence Herron - Seniors Action Quebec (SAQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

La communauté anglophone des Îles prend des mesures afin de mitiger les effets de la pandémie du COVID-19 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

The English-speaking Community of the Magdalen Islands Takes Action to Mitigate the Effects of the COVID-19 Pandemic - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Neighbours Newsletter : April 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

FAQ Regarding the Canadian Emergency Response Benefit (CERB) Program - McSween, Pierre-Yves (2020)
Disclaimer: This document has been prepared with the information in public circulation as of March 26, 2020. This is not an official communication from the government and information presented here is not to be used as proof of eligibility. YES has translated and edited the original text for clarity. This information is provided solely as a resource. As this is an evolving document, the user of this information is responsible for determining and verifying the accuracy of the data presented here and how it is used.

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

Impact Report 2019-2020 - 4Korners (2020)

Rapport d'impact 2019-2020 - 4Korners (2020)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2020)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)

Enhancing Regional Capacity / Reforcer la capitacité communautaire régionale - Community Health and Social Services Network (CHSSN) (2020)

Adapting Services During the Pandemic : The Example of Jeffery Hale-Saint Brigid's and Its Partners - Duchesne, Anne (2020)

[Update to Parents Regarding Return to School for Fall 2020] - English Parents' Committee Association (EPCA) (2020)

Jackie Robinson Golf Tournament - Gunning, Glen; Piggot, Sylvia (BASF) (2020)

An Uncertain Future for the Future of Québec : Policy Brief on the Under Employment of English-speaking Youth in the Quebec Civil Service - Lawler, Madeleine (Youth for Youth Québec (Y4Y Québec), 2020)
Since the start of the COVID-19 global pandemic, post-secondary students have been amongst the hardest hit economically. In the span of two months, the unemployment rate amongst Canadian post-secondary students almost doubled, and less than a quarter of previously employed students continued working their regular hours. The global pandemic further exacerbated pre-existing issues of economic vulnerability and underemployment amongst English-speaking youth in Quebec. According to a 2018 CHSSN report, the unemployment rate amongst English-speaking youth was 13.3%, whereas that of their Frenchspeaking counterparts was 9.8%.2 Across different industries, the under-employment of Englishspeaking youth is perhaps the most pitiful within the Quebec civil service. In general, anglophones have represented between 0.7% and 1% of the provincial civil service for nearly half a century, despite representing 7.4% of the population in 2016

Communications During COVID Time - NDG Community Council (NDGCC) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

Covid-19 : Considerations When Deciding to Move Seniors from Residences or CHSLDS - Seniors Action Quebec (SAQ) (2020)

Questions Pertinentes à poser à une résidence pour aînes pendant la pandémie de Covid-19 - Seniors Action Quebec (SAQ) (2020)

Tips on Helping Seniors Deal with Isolation During Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

What to Ask a Senior's Residence During the Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

2019-2020 Annual Report - The English Speaking Catholic Council (ESCC) (2020)

Small Business Resource Guide - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, we have compiled a resource guide for small businesses to help you navigate these challenging times.